Deviant or Wrong? The Effects of Norm Information on the Efficacy of Punishment - Cristina Bicchieri; Eugen Dimant; Erte Xiao (Center for Economic Studies and Ifo Institute (CESifo), 2021)
Research examining the effect of weak punishment on conformity indicates that punishment can backfire and lead to suboptimal social outcomes. We examine whether this effect is due to a lack of perceived legitimacy of rule enforcement, which would enable agents to justify selfish behavior. We address the question of legitimacy by shedding light upon the importance of social norms and their interplay with weak punishment in the context of a trust game. Across six conditions, we systematically vary the combination of existence of weak punishment and norm information. Norm information may refer either to what most others do (empirical) or to what most others deem appropriate (normative). We show that in isolation, neither weak punishment nor empirical/normative information increase prosocial, reciprocal behavior. We instead find that reciprocity significantly increases when normative information and weak punishment are combined, but only when compliance is relatively cheap. When compliance is more costly, we find that the combination of punishment and generic empirical information about others' conformity can have detrimental effects. In additional experiments, we show that this negative effect can be attributed to the punishment being perceived as unjustified, at least in some individuals. Our results have important implications for researchers and practitioners alike.
Keywords: C91; D03; D73; H26; 330; conformity; punishment; social norms; trust